CDF simulation of crude oil homogenization in pilot plant scale - Castro Gualdrón, Jesús Alberto; Díaz Mateus, Fabián Andrey; Abreu Mora, Leonel Andres (CT&F - Ciencia, Tecnología y Futuro, 2013)
The homogenization of different crude oils in a pilot plant tank is simulated using Computational Fluid Dynamics (CFD) commercial code. The models are inherently transient since all simulations start from a time zero where the crudes are completely separated to a final time of full homogenization. The tank is agitated with a small impeller and a two-phase model is used in the simulations in order to see the mixing process and calculate the properties of the blend based on the volume fractions. The effect of the mesh size and time step size are studied since in this type of simulations the computational effort becomes a major parameter and has to be reduced to a minimum. Experimental data taken from two different points in the tank at regular time intervals are available to compare the results of the simulations, concluding in good agreement.